Implementasi Metode Mengajar Mastery Learning dalam Pembelajaran Pendidikan Agama Katolik di Era Society 5.0 - Yessi Florentina Pasaribu; Sergius Lay (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This research is entitled Implementation of Mastery Learning Teaching Methods in Catholic Religion Learning in the Era of Society 5.0. The research method used in this paper is library research. Meanwhile, the aim of this research is to find out one learning method that can be used by educators, namely the mastery learning method. Specifically, to find out how to implement mastery learning teaching methods in Catholic religious learning in the era of society 5.0. The mastery learning method or complete learning model is a learning model that presents an interesting and concise way to improve student achievement in a more satisfying direction. The stages in implementing the mastery learning method are orientation, presentation, structured practice, guided practice and independent practice. Implementation of the mastery learning method in Catholic religious education in the era of society 5.0 is an effective method used in Catholic religious learning, because the learning process is structured and begins with an orientation stage, until students truly master the subject matter taught by the teacher. In this era of society 5.0, a teacher must be able to use available information technology to facilitate the learning process. By using the mastery learning method in Catholic religious education, students will more fully understand what is being studied and can form their faith in accordance with the teachings of the Catholic religion.